Soil physical and chemical properties in urban park irrigated with treated wastewater - Flores-Margez, Juan Pedro; Rojas-Villalobos, Hugo Luis; Osuna-Avila, Pedro (Ecosistemas y Recursos Agropecuarios, 2025)
The lack of information on the physical and chemical properties of the soil in urban parks is a technical limitation for decision making. The objective was to analyze soil properties to measure the impact of irrigation with treated wastewater, and recreational activity. The bulk density varied between areas, 42% of the soils had a sandy loam texture and 34% were loamy. The pH varied from 6.83 to 8.56, and soil salinity was between 1.3 and 14.0 dS m-1, N was from 1.0 to 157.3 mg kg-1 and predominated in the form of N-nitrates, but phosphorus was from 4.7 to 471 mg kg-1, NTK was from 377 to 1760 mg kg-1, the OM content was between 0.05 and 3.5%, and correlation between the NTK and OM was found. Variability among soil parameters was attributed to irregular irrigation practices with wastewater, and human activity.
Keywords: Alkalinity; granulometry; nutrient; organic matter; salinity